Help! We need a title! - Tullet, Hervé (Candlewick Press, 2014)
Take a peek inside this book and you'll find some characters (though they're still a bit sketchy). They'll be perplexed to see you, so they'll quickly try to track down their author (who has a lot more work to do). What you won't find is a story, or a title, because, guess what? The book isn't finished yet! But surely the author must have a story to tell? In this charming "meta" picture book, children of all ages are encouraged to interact with a book still in the process of being invented. And that's a story in itself!